Xenobiotic Detoxification Genes and Their Role in the Development of Pneumonia - L. Ye. Salnikova; T. V. Smelaya; V. V. Moroz; A. M. Golubev; N. Kh., Ponasenkov; R. V. Khomenko; I. V. Kharlamova; N. Sh. Lapteva; G. I. Kuznetsova; G. G. Poroshenko; A. V. Rubanovich (Общая реаниматология, 2008)
Objective: to analyze DNA polymorphism in inpatients with pneumonia. Subjects and methods. Group 1 consisted of 99 patients with acute community-acquired pneumonia (CAP). Group 2 included 95 patients with severe concomitant injury, including wounds (n=63) and generalized peritonitis (n=32). Among Group 2 patients, the authors singled out two subgroups: 2A comprising 57 patients with nosocomial pneumonia (NP) and 2B including 38 patients without NP. A control group was composed of 160 apparently healthy individuals. Polymerase chain reaction genotyping was carried out for the polymorphic genes controlling xenobiotic detoxification (such as GSTM1, GSTT1, GSTP1, and CYP1A1) and the MTHFR gene that is responsible for DNA synthesis and methylation. Results. Predisposition to acute CAP has been shown for the carriers of a minor allele (4889G) at the CYP1A1 locus: 12.7% versus 5.4% in the controls (p=0.034; OR=2.6); In Group 1 patients, the development of complications (toxic myocarditis, pleuritis, pleural empyema, toxic nephropathy) is most probable for a combination of GSTT1 + GSTM1 0/0 genotypes (OR=3.2; p=0.010 versus the control group). It has been established that in severe injury, peritonitis (2B), NP does not develop statistically significantly in 61.1% of cases with the GSTM1 + GSTT1 + genotype versus 38.8% in the controls (p=0.022) or versus 37.5% in subgroup 2A (p=0.045; OR=2.6). Key words: acute community-acquired pneumonia, nosocomial pneumonia, gene polymorphism.